2003
DOI: 10.1053/rmed.2003.1507
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 in sputum correlates with airway hyperresponsiveness to methacholine

Abstract: According to our results IL-17 is probably not involved in pathogenesis of stable COPD, but it may play a role in people with airway hyperresponsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
240
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(258 citation statements)
references
References 34 publications
9
240
1
8
Order By: Relevance
“…[32][33][34][35][36] IL-17A also plays a role in human asthmatic patients and in airways of allergic animals. 18,28,30,[37][38][39] Studies have found that in patients with moderate-to-severe asthma, neutrophils are found to be more abundant than eosinophils in the bronchoalveolar lavage fluid. 30,31,40 IL-17A can promote neutrophil recruitment, which might contribute to certain asthmatic phenotypes characterized by both high neutrophil counts and IL-17A expression.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36] IL-17A also plays a role in human asthmatic patients and in airways of allergic animals. 18,28,30,[37][38][39] Studies have found that in patients with moderate-to-severe asthma, neutrophils are found to be more abundant than eosinophils in the bronchoalveolar lavage fluid. 30,31,40 IL-17A can promote neutrophil recruitment, which might contribute to certain asthmatic phenotypes characterized by both high neutrophil counts and IL-17A expression.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, in humans increased expression of IL-17A and IL-17F has been shown in bronchial submucosa of moderate to severe asthma, and the evaluation of induced sputum in patients with asthma revealed that neutrophilic inflammation was frequently present, particularly in the severe forms of disease (75,79,80). Furthermore, it has been reported that increased AHR in response to methacholine in patients with asthma positively correlates with IL-17A levels in the sputum (81). Finally, a polymorphism in IL-17F that results in a loss-of-function mutation is inversely related to asthma risk (82).…”
Section: Th17 Lymphocytes and Asthmamentioning
confidence: 99%
“…Inactivation of protease activity led to reduction in allergic parameters. These results demonstrate that proteolytic activity of Per a 10 potentiates its allergenicity.There was an increase in levels of IL-17A in the sputum of severe asthmatics [23] and may act as a marker and risk factor for severe asthma [24]. Previously, it was shown that GC frass induces IL-17A secretion in a PAR-2-dependent manner.…”
mentioning
confidence: 91%